(untitled) (Biological Sciences - PJSIR, 2003)
Potassium (K) deficiency exists in different rice growing areas of Malaysia. A study on K adsorption was carried out in three Malaysian rice soils (Guar, Hutan and Kangar series) using six levels of K (0.00, 28.77, 33.57, 38.37, 43.16 and 47.96 mmol kg-1). The data on K adsorption were fitted into Langmuir, Freundlich, and Temkin adsorption equations. Adsorption data were also correlated with pH, cation exchange capacity and organic matter content of the soils. Potassium adsorption increased linearly with increasing level of added K in all the three soils. The rate of increase was the highest in Guar series followed by Kangar and Hutan series, respectively. Potassium adsorption in two soils (Hutan and Kangar) fitted into Langmuir equation while the adsorption data in Guar series did not fit into this equation. Adsorption data in none of the soils fitted well in Freundlich and Temkin adsorption equations. Correlation between K adsorption and pH was significant (r = 0.881), whereas, correlation of K adsorption with either organic matter content or cation exchange capacity was non-significant. The results of this study indicated that K adsorption is mainly dependent on soil pH. In soils with higher adsorption capacity, more K fertilizer may be needed to get immediate crop response.